2012
DOI: 10.1525/mp.2012.30.1.71
|View full text |Cite
|
Sign up to set email alerts
|

When the Eye Listens: A Meta-analysis of How Audio-visual Presentation Enhances the Appreciation of Music Performance

Abstract: the visual component of music performance as experienced in a live concert is of central importance for the appreciation of music performance. However, up until now the influence of the visual component on the evaluation of music performance has remained unquantified in terms of effect size estimations. Based on a meta-analysis of 15 aggregated studies on audio-visual music perception (total N = 1,298), we calculated the average effect size of the visual component in music performance appreciation by subtracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
101
4
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 34 publications
7
101
4
5
Order By: Relevance
“…On the basis that music is a multisensory phenomenon [34], visual kinematic information from an event (e.g. performer actions) has been documented to be a crucial factor in the communication of meaning [28] and in the emotional reactions evoked [34] within the audience. Nonetheless, electronic music performances are often sensor or laptop-based, which are not always visible to the public and whose usage does not require big gestures and actions from the performer.…”
Section: Audience Researchmentioning
confidence: 99%
“…On the basis that music is a multisensory phenomenon [34], visual kinematic information from an event (e.g. performer actions) has been documented to be a crucial factor in the communication of meaning [28] and in the emotional reactions evoked [34] within the audience. Nonetheless, electronic music performances are often sensor or laptop-based, which are not always visible to the public and whose usage does not require big gestures and actions from the performer.…”
Section: Audience Researchmentioning
confidence: 99%
“…Various studies from this first line of research have demonstrated the fundamental principle that visual information accompanying the act of listening to music can influence what we hear and, at times, heighten our enjoyment of it (Behne & Wollner, 2011;for reviews, see Platz &Kopiez, 2012 andSchutz, 2008). Schutz and Lipscomb (2007), for example, report an illusion in which the duration of short-length tones played by a marimba player was perceived by participants as longer when accompanied by a video of the performer making a longer, larger performance gesture.…”
Section: Empirical Research On Audiovisual Music Perceptionmentioning
confidence: 99%
“…Average ratings of congruence were found to be significantly higher for the matched stimuli than the mismatched stimuli. Platz and Kopiez [25] conducted a meta-analysis of studies into the influence of the visual modality on evaluations of music performance. Aggregating the results from 15 previous studies revealed that the influence of the visual component has a medium effect size (quantified using Cohen's d).…”
Section: Introductionmentioning
confidence: 99%